Ocular Hypotensive Lipids: A Comprehensive Review - Surbi Taneja; Harsh Kumar; Swati Singh; Tripti Johri; Anushree Baid (Delhi Journal of Ophthalmology)
Prostaglandin analogs (PGA’s) or ocular hypotensive lipids are a significant class of medications primarily used in the management of glaucoma and ocular hypertension. Since their introduction in the late 20th century, these compounds have revolutionized treatment protocols, offering a potent and effective means of lowering intraocular pressure (IOP). By mimicking the activity of naturally occurring prostaglandins, these analogs enhance the outflow of aqueous humor from the eye, thus reducing IOP and preventing damage to the optic nerve. Their role in clinical practice has expanded due to their relatively favorable side effect profile and once-daily dosing regimen, which promotes patient adherence. This review article delves into the pharmacodynamics and pharmacokinetics of the PGA’s, including latanoprost, bimatoprost, travoprost, tafluprost, and unoprostone. In addition, this article explores the molecular mechanisms underlying their therapeutic effects, the latest clinical trial data, and comparative studies that highlight their relative benefits and limitations. By synthesizing current knowledge and recent advancements, this article aims to provide a comprehensive overview for healthcare professionals, researchers, and students interested in the evolving landscape of glaucoma treatment.